バイカル湖表層型メタンハイドレート賦存堆積土の地盤工学的性質 - 片岡, 沙都紀; 山下, 聡; 南, 尚嗣; 西尾, 伸也; 安部, 透; 横山, 幸也; 兵動, 正幸 (Jiban Kogaku Janaru (Japanese Geotechnical Journal), 2007)
2005，2006 年に，ロシア・バイカル湖にて実施した表層型メタンハイドレート賦存地盤調査から，湖底表層土の工学的特性について検討を行った。調査ではメタンハイドレートを含む湖底表層の堆積土採取，コア観察および現地船上試験（コーン貫入試験，ベーンせん断試験，ベンダーエレメント試験，一軸圧縮試験）を行った。その際，試料はメタンハイドレート含有堆積土のほかに，音波探査によりメタンハイドレートの存在が確認されなかった地盤からも採取し，各種試験での比較を行った。その結果，メタンハイドレートを含む地盤の表層堆積土は，メタンハイドレートが存在していない地盤の試料に比べて，測定値が堆積深度に依存せず，低い値を示した。この原因として，ガスや水の湧出による地盤の撹乱と試料採取時の応力解放が関係していると考えられた。 The site investigation of the shallow type methane hydrate-bearing ground was performed on the Lake Baikal, Russia, in 2005 and 2006, and the geotechnical properties of the bottom sediment were examined. In the investigation, sediments with methane hydrates were sampled, and several kinds of tests (cone penetration, vane shear, bender element, uniaxial compression tests) were performed on the board. At the same time, samples were also retrieved from the grounds without methane hydrates. Then, the soil strengths and physical properties for both samples were compared. As a result, it was found that the soil strengths of surface sediments with methane hydrates were lower than those without methane hydrates regardless of the depth. It would seem that this is because the effect of the disturbance by emission of gas and water and pressure release during the sampling. application/pdf journal article